PENGEMBANGAN E-LKPD BERBANTUAN MEDIA WORDWALL MENGGUNAKAN MODEL PROBLEM BASED LEARNING PADA PEMBELAJARAN IPAS DI KELAS lV SEKOLAH DASAR - Wulandari, Cici; Erita, Yeni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is motivated by the demands of 21st-century learning which requires the integration of digital technology to improve the quality of the teaching and learning process in elementary schools. Science and Social Studies (IPAS) learning in the Merdeka Curriculum is expected to encourage students to think critically, solve problems, and actively participate in learning activities. However, based on observations and interviews conducted in several elementary schools in Region II of Lubuk Kilangan District, Padang City, it was found that learning activities were still dominated by conventional teaching methods and printed worksheets, resulting in limited student engagement. In addition, the use of digital technology in learning has not been systematically integrated with innovative learning models such as Problem Based Learning (PBL). Therefore, this study aims to develop an electronic student worksheet (E-LKPD) assisted by the Wordwall media using the Problem Based Learning model in IPAS learning for fourth-grade elementary school students. The developed E-LKPD is designed to facilitate students in identifying problems, conducting investigations, collaborating in discussions, and presenting solutions systematically through interactive digital activities. Wordwall is utilized to provide educational games and interactive learning activities that can enhance students’ motivation and engagement in the learning process. By integrating the PBL model with Wordwall media, the developed E-LKPD is expected to become an innovative learning medium that supports more effective IPAS learning, improves students’ critical thinking skills, and encourages active participation in classroom activities. The results of this development are expected to serve as an alternative digital learning medium that is practical, engaging, and relevant to the needs of learning in the digital era.